2015
DOI: 10.1111/bjh.13430
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of dose‐dense and dose‐intense ABVD for high‐risk patients with advanced Hodgkin lymphoma: reply to D'Arco et al

Abstract: Effect of initial treatment strategy on survival of patients with advanced-stage Hodgkin's lymphoma: a systematic review and network metaanalysis. The Lancet Oncology, 14, 943-952.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…28,29 More recently the incorporation of novel agents in the front line ABVD backbone as CPIs or BV have showed that it is possible to increase the efficacy of first line HL therapy without a detrimental effect of the patients safety. 17,[30][31][32] Of note none of these recent trials included a response adapted approach in the design of the experimental therapy, leading to a wrong conclusion that treatment personalization could be abandoned. A return to the one size fits all approach in HL, even if resulting in an easier management of therapy, in our opinion represents an oversimplified approach.…”
Section: Characteristicsmentioning
confidence: 99%
“…28,29 More recently the incorporation of novel agents in the front line ABVD backbone as CPIs or BV have showed that it is possible to increase the efficacy of first line HL therapy without a detrimental effect of the patients safety. 17,[30][31][32] Of note none of these recent trials included a response adapted approach in the design of the experimental therapy, leading to a wrong conclusion that treatment personalization could be abandoned. A return to the one size fits all approach in HL, even if resulting in an easier management of therapy, in our opinion represents an oversimplified approach.…”
Section: Characteristicsmentioning
confidence: 99%